2016
DOI: 10.1016/j.apjtm.2016.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Regulating effect of activated NF-κB on edema induced by traumatic brain injury of rats

Abstract: The results show that the activation of NF-κB in astrocytes is a key factor in the process of cerebral edema after TBI of rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…First, it has been shown to be involved in the pathogenesis of TBI. 38,39 Second, NF-jB/p65 is a wellestablished priming signal for NLRP3 inflammasomes. 40 Transcriptional priming of inflammasome constituents like caspase-1 is an essential prerequisite step for further NLRP3 inflammasome activation and subsequent IL-1b maturation.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been shown to be involved in the pathogenesis of TBI. 38,39 Second, NF-jB/p65 is a wellestablished priming signal for NLRP3 inflammasomes. 40 Transcriptional priming of inflammasome constituents like caspase-1 is an essential prerequisite step for further NLRP3 inflammasome activation and subsequent IL-1b maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of recent studies have found that pharmacological treatments that directly or indirectly target this inflammasome can reduce its activity following moderate-to-severe TBI. These treatments are broadly broken into four groups: (i) treatments derived from naturally occurring compounds (e.g., mangiferin [83], omega-3 fatty acids [71], and apocynin [84]); (ii) repurposed medications (e.g., propofol [85], and telmisartan [86]); (iii) inhibitors of NLRP3-associated molecules (e.g., ASC antibodies [87], NF-κB inhibitor, Bay 11-7082 [88][89][90][91]); and (iv) specific NLRP3 inflammasome inhibitors (e.g., MCC950 [69], JC-124 [92]). While the first three treatment categories have been shown to decrease NLRP3 inflammasome activity as well as demonstrating a neuroprotective effect, they do not target NLRP3 activation specifically.…”
Section: Nlrp3 As a Therapeutic Target For Tbimentioning
confidence: 99%
“…NF-κB comprises a group of transcription factors in eukaryocytes, which is distributed widely in the nervous system (23). Under physiological conditions, it does not have transcriptional activities.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB and IκB are activated and shift into the nucleus from the cytoplasm (24). Studies have found that NF-κB is activated in rats with SCP at an early stage (23,25). Activated NF-κB can be found in the cytoplasm and cell nuclei of neurons 24 h following injury (25).…”
Section: Discussionmentioning
confidence: 99%